THE CORRELATION BETWEEN PROPROTEIN CONVERTASE SUBTILISIN/KEXIN TYPE 9 LEVELS AND LOW-DENSITY LIPOPROTEIN LEVELS IN CHRONIC KIDNEY DISEASE - Decroli, Eva; Viotra, Deka; Aprilia, Dinda; Kam, Alexander; Shiddiq, Akbar (E-Jurnal Medika Udayana; Vol 14 No 5 (2025): E-Jurnal Medika Udayana, 2025)
ABSTRACT Introduction : Chronic kidney disease (CKD) patients have an increased mortality rate when accompanied by cardiovascular disease due to dyslipidemia. Elevated PCSK9 levels in CKD lead to increased LDL cholesterol. This study aims to evaluate the correlation between PCSK9 levels and serum LDL cholesterol in CKD patients. Methods: This observational analytical study used a cross-sectional approach. Subjects were patients with CKD aged 18-59 years who were treated at the Inpatient Installation of the Internal Medicine Department of RSUP Dr. M. Djamil Padang. Statistical analysis was performed using SPSS. Results: The study included 30 CKD patients, of whom 56.6% were male. The average age was 50.03 (6.7) years, with a BMI of 23.12 kg/m² (5.1). Obesity was found in 40% of the sample. Average cholesterol was 169.3 (60.13) mg/dL, HDL cholesterol was 29.03 (14.15) mg/dL, triglycerides were 185.13 (82.4) mg/dL, and creatinine was elevated at 9.2 (5.15) mg/dL. Average glomerular filtration rate below 15 mL/min/1.73 m² was 9.55 (9.38) mL/min. Most patients had CKD stage 5 (83.33%). The data showed a weak, statistically insignificant positive correlation (r=0.011, p>0.05) between serum PCSK9 levels and LDL cholesterol in CKD patients. Conclusion: There is no significant correlation between PCSK9 levels and serum LDL cholesterol in CKD patients. Keywords : LDL Cholesterol, PCSK9, Chronic Kidney Disease